Review artikel: analisis faktor yang mempengaruhi kejadian pneumonia pada bayi dan balita - Sholih, Mally Ghinan; Mulki, Munir Alinu; Julianti, Nurlia; Jannah, Roudotul; Indriyani, Yuni Lili (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Pneumonia is an infection of the lower respiratory tract which is the main cause of death in toddlers and children. Although there is a lot of information about risk factors for pneumonia, there is information that is not presented in detail and specifically. The purpose of this review article is to provide insight into the risk factors that cause pneumonia in babies and toddlers, making us more alert and aware of the importance of preventing and treating pneumonia, especially in babies and toddlers. The review method for this article is a literature review. The database comes from national and international journals via Google Scholar and PubMed databases published in the years 2013-2023. The results and discussion of this review include information about pneumonia, risk factors for pneumonia, and factors causing pneumonia in infants and toddlers. Based on the articles that have been reviewed, it shows that the factors that influence the incidence of pneumonia are exposure to cigarette smoke, LBW, nutritional status, gender, and history of exclusive breastfeeding.